ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI BUNYI DAN GELOMBANG BAGI SISWA SEKOLAH DASAR - Siti Hafiza; Rosila Antika; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
This research is motivated by the low level of student understanding of sound and waves in Natural and Social Sciences (IPAS), particularly among fourth-grade students at SD Negeri 050711 Pasar Gunung, Secanggang District, Langkat Regency, North Sumatra. The main problem faced is the lack of use of contextual and interactive learning media, making it difficult for students to understand abstract concepts such as the properties of waves and the direction of sound propagation. This study aims to analyze the effectiveness of using visual and demonstrative learning media in improving students' conceptual understanding. The method used is a qualitative descriptive approach with data collection techniques through direct observation, interviews with teachers and students, and documentation of learning activities. The results show that the use of appropriate learning media such as videos, visual aids, and simple simulations can increase student interest in learning, encourage active participation, and clarify the concepts taught. It can be concluded that learning media plays a crucial role in helping students understand abstract IPAS material. Therefore, teachers are advised to continue developing creative and innovative learning media to make the teaching and learning process more effective and meaningful.